2022
DOI: 10.1007/s11739-021-02899-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging underlies heterogeneity between comorbidity and multimorbidity frameworks

Abstract: Studies exploring differences between comorbidity (i.e., the co-existence of additional diseases with reference to an index condition) and multimorbidity (i.e., the presence of multiple diseases in which no one holds priority) are lacking. In this single-center, observational study conducted in an academic, internal medicine ward, we aimed to evaluate the prevalence of patients with two or more multiple chronic conditions (MCC), comorbidity, or multimorbidity, correlating them with other patients' characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Male patients aged 65 years or younger felt obligated to support themselves, and their family members relied on their limited income, This is due to the traditional Chinese view of men as career-oriented and providing a pivotal part of family income ( Su et al, 2019 ; Wu et al, 2022 ), therefore, men had experienced higher economic burdens and lower levels of resilience. Patients aged 71 years and older were more likely to have multimorbidity ( Lenti et al, 2022 ), and their physical function, physical activity, psychological state, and quality of life were all lower ( Seong et al, 2022 ). While, this finding is at odds with earlier research, which indicated neither an upgrading in resilience with age ( Harms et al, 2019 ) nor a decrease with age ( Tamura et al, 2021 ; Musich et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male patients aged 65 years or younger felt obligated to support themselves, and their family members relied on their limited income, This is due to the traditional Chinese view of men as career-oriented and providing a pivotal part of family income ( Su et al, 2019 ; Wu et al, 2022 ), therefore, men had experienced higher economic burdens and lower levels of resilience. Patients aged 71 years and older were more likely to have multimorbidity ( Lenti et al, 2022 ), and their physical function, physical activity, psychological state, and quality of life were all lower ( Seong et al, 2022 ). While, this finding is at odds with earlier research, which indicated neither an upgrading in resilience with age ( Harms et al, 2019 ) nor a decrease with age ( Tamura et al, 2021 ; Musich et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This well agrees with the results of Ji and colleagues [ 42 ]. Alternatively, with respect to MMSE cognitive status, the binary tree indicated that only the number of daily drugs, considered an index of comorbidity [ 43 ], and leisure activities significantly influenced the frailty status with any impact of MMSE itself, showing the higher proportion of frail individuals among those with a higher number of drugs and without leisure activities, while the most robust group was retrieved from those with a lower number of daily drugs. The whole regression analysis reported a significant association also for MMSE, and a recent review also suggests a bidirectional relationship between frailty and cognitive impairment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,8,9,13,15,16 In our study, multimorbidity, Early mortality in hospitalised patients as assessed by CIRS, was not correlated with either in-hospital or post-discharge mortality. This is probably because, as already shown in the SMAC study, 39 upon admission, the majority of patients had a CIRS comorbidity index >3, and hence this factor was far too common to highlight heterogeneity within the population. In other studies, multimorbidity had different impacts on early mortality, sometimes being significantly associated, as in Smolin et al, Han et al and Aljishi et al (according to the Charlson Comorbidity Index), 7,8,15 or had no significant effect, as in Perysinaki et al (according to the simple enumeration of diseases).…”
Section: Odds Ratio 95% CI P-valuementioning
confidence: 90%